Transparency, Governance, and Public Service Management: Challenges of Citizen Participation in Ecatepec de Morelos - Alan Jesús Torres-Sandoval; María Elena Tavera-Cortés; Marco Aurelio Acevedo-Ortiz; Yolanda Donají Ortiz-Hernández (Administrative Sciences)
Innovation in public sector management is essential for improving service delivery and strengthening citizen trust. However, in highly populated municipalities with budgetary constraints, such as Ecatepec de Morelos, administrative opacity and inefficiencies in the provision of essential services pose significant structural challenges. This study examines the relationship between citizens’ perceptions of public resource management and the quality of municipal services, with a particular focus on transparency and accountability. Through perception surveys, statistical analysis, and documentary review, the research identifies operational barriers affecting the provision of basic services such as potable water, sanitation, and public lighting. The findings reveal high levels of citizen dissatisfaction and distrust in local institutions, highlighting the urgent need to implement innovative strategies to optimize resource allocation and enhance municipal governance. This study contributes to the ongoing discussion on public sector modernization by emphasizing the need for participatory decision-making mechanisms, strengthened transparency, and the adoption of best practices in municipal management.